A Case Report of Harm‐Related Obsessions in Pediatric Obsessive‐Compulsive Disorder. Issue 11 (18th September 2016) - Wu, Monica S.; Storch, Eric A.
Abstract : Harm‐related, or "aggressive, " obsessions are a symptom subtype in obsessive‐compulsive disorder (OCD). Given the violent nature of these thoughts, the stark contrast between the child's character and the content of these obsessions often results in high levels of distress for not only the patient but also the family. This case report illustrates the application of family‐based exposure and response prevention (ERP) for a 15‐year‐old male presenting with harm‐related obsessions and mild depressive symptoms secondary to the OCD. The obsessions primarily revolved around the fear of acting on unwanted impulses (e.g., stabbing a family member, pushing a friend onto oncoming traffic), and the compulsions entailed avoidance (both mental and physical), excessive reassurance seeking, and ritualistic confessions. The client underwent a 14‐week course of ERP involving repeated imaginal and in vivo exposures and behavioral activation to alleviate depressive symptoms. Significant improvements in obsessive‐compulsive symptom severity and depressive symptoms were observed posttreatment, elucidating the efficacy of treating harm‐related obsessions with a course of ERP.